Around-the-objective total internal reflection fluorescence microscopy - Burghardt, Thomas P. (2009)
Total internal reflection fluorescence (TIRF) microscopy uses the evanescent field on the aqueous side of a glass/aqueous interface to selectively illuminate fluorophores within ~100 nm of the interface. Applications of the method include epi-illumination TIRF, where the exciting light is refracted by the microscope objective to impinge on the interface at incidence angles beyond critical angle, and prism-based TIRF, where exciting light propagates to the interface externally to the microscope optics. The former has higher background autofluorescence from the glass elements of the objective where the exciting beam is focused, and the latter does not collect near-field emission from the fluorescent sample. Around-the-objective TIRF, developed here, creates the evanescent field by conditioning the exciting laser beam to propagate through the submillimeter gap created by the oil immersion high numerical aperture objective and the glass coverslip. The approach eliminates background light due to the admission of the laser excitation to the microscopic optics while collecting near-field emission from the dipoles excited by the ~50 nm deep evanescent field.